Diffuse necrotizing pneumonia, cavitations and hemoptysis: A case of sweet syndrome - Felicia Montero-Arias; Randall Rojas-Varela; Abril Rodriguez-Loria; Ricardo Ramos-Castro; Simon Belilty-Montvelisky; Rodrigo Cartin-Ceba (Respiratory Medicine Case Reports)
A 33-year-old man presented with a 1-week history of odynophagia, fever, and dyspnea. Initial chest computed tomography (CT) revealed multiple bilateral consolidations predominantly in the lower lobes. Laboratory investigations revealed leukocytosis, while cultures remained negative and the patient was started on antibiotics for suspected community-acquired pneumonia. Despite this, his condition deteriorated, with follow-up CT showing necrotizing pneumonia and cavitations. He subsequently developed violaceous papular lesions on the upper extremities, and skin biopsy confirmed Sweet syndrome, characterized by dermal neutrophilic infiltration without leukocytoclastic vasculitis. Corticosteroid therapy was initiated; however, the patient succumbed to massive hemoptysis one month after admission. This case highlights the importance of considering systemic inflammatory conditions like Sweet syndrome in the differential diagnosis of culture-negative pneumonia.